Search Costs and Investment in Quality1. (December 2015) - Fishman, Arthur; Levy, Nadav
Abstract : In this paper we analyze how lower search costs affect firms' incentives to invest in quality. We identify two conflicting effects. On the one hand, lower search costs increase incentives to invest in quality by eroding the market share of low quality firms and increasing the market share of high quality firms. On the other hand, by intensifying price competition, lower search costs adversely affect high quality firms more than low quality firms. The net effect of a change in the search cost on quality is shown to depend on the initial quality distribution. There is a critical value such that, if the proportion of high quality firms is initially below this value, lower search costs increase this proportion, whereas if the initial quality is above this value, lower search cost decreases the proportion of high quality firms. We show that our results are consistent with a 'superstar effect.'